Simultaneous quantitation of folic acid and 5-methyltetrahydrofolic acid in human plasma by HPLCâMS/MS and its application to a pharmacokinetic study - Xiao-Hong Zheng; Li-Yuan Jiang; Lan-Ting Zhao; Quan-Ying Zhang; Li Ding (Elsevier, 2015)
A sensitive method based on high-performance liquid chromatographyâtandem mass spectrometry (LCâMS/MS) has been developed for the simultaneous determination of folic acid (FA) and its active metabolite, 5-methyltetrahydrofolic acid (5-M-THF), in human plasma. The analytes were extracted from plasma with methanol solution containing 10Â mg/mL of 2-mercaptoethanol and 0.025% (v/v) ammonium hydroxide. FA and 5-M-THF were more stable after the addition of 2-mercaptoethanol and ammonium hydroxide in the sample preparation procedures of this study than they were in the previously published methods. Chromatographic separation was performed on a Hedera ODS-2 column using a gradient elution system of acetonitrile and 1Â mM ammonium acetate buffer solution containing 0.6% formic acid as mobile phase. LCâMS/MS was carried out with an ESI ion-source and operated in the multiple reaction monitoring (MRM) mode. The assay was linear over the concentration ranges of 0.249â19.9Â ng/mL for FA, and 5.05â50.5Â ng/mL for 5-M-THF. The developed LCâMS/MS method offers increased sensitivity for quantification of FA and 5-M-THF in human plasma and was applicable to a pharmacokinetic study of FA and 5-M-THF. Keywords: Folic acid, 5-Methyltetrahydrofolic acid, 2-Mercaptoethanol, LCâMS/MS, Pharmacokinetics